SOCIOLINGUISTIC FOUNDATIONS AND CHARACTERISTICS OF WORDS BORROWED FROM ENGLISH INTO GERMAN (Conference Zone, 2022)
This article provides information about the sociolinguistic features of borrowed words, in particular, words that have been borrowed from English to German, as well as the methods of studying these features.